Social care, service users and user involvement - Carr, Sarah, 1971-; Beresford, Peter (Research highlights in social work, 2012)
Social Care, Service Users and User Involvement provides a definitive introduction to practical, philosophical and theoretical issues at the heart of user involvement. This book provides an accessible account of the latest research findings regarding user involvement on three levels: the delivery and provision of services, practice and practitioners, and research and evaluation. It explores a wide range of service user needs and concerns, including the latest developments in personalisation and the effect of the Equality Act 2010. First-hand accounts illustrate the range of issues and service.